Publication Trends and Development of Critical Thinking Concepts in Elementary Education: A Bibliometric Review - Maria Oktaviani, Anna; Marini, Arita; Supena, Asep (Exploration in Early Childhood Research, 2024)
Critical thinking is becoming an increasingly important skill in the 21st century, characterized by technological advances, globalization, and information complexity. To determine research trends related to critical thinking skills, this research uses the R Package and carries out bibliometric analysis. The metadata used comes from SCOPUS from 2014 to 2024. The data was analyzed with the keywords "critical thinking" and "basic education" to find publication trends, the most prolific authors, the most active institutions, and the most popular research topics and methods. The results of the analysis highlight the evolution and changes in understanding and approaches to critical thinking in the context of basic education over the period studied. This research provides valuable insights for academics, researchers, and educational practitioners to understand the dynamics of the development of critical thinking in basic education literature. It also offers avenues for additional research.